Dampak Globalisasi terhadap Pola Sosialisasi Pendidikan di Indonesia - Mukhamad Zidane Abiansyah; Nur Khasanah (Yayasan Al-Afif, 2025)
The process of globalization has brought about significant changes in various aspects of life, including the education sector in Indonesia. Advances in information and communication technology have influenced the way educational socialization occurs, impacting the learning process, value systems, and the roles of socialization agents such as family, school, and community. This research aims to analyze the influence of globalization on the pattern of educational socialization in Indonesia, as well as explore the challenges arising from the secularization and commercialization of education. The method used in this study is a literature review with a descriptive qualitative approach through mapping various relevant books, scientific journals, and library sources. The research findings indicate that globalization has positive impacts, such as technology-based learning innovation, increased access to information, and the strengthening of human resource competencies. However, on the other hand, globalization also presents negative impacts, such as inequality in educational access, the commercialization of educational institutions, and the erosion of moral and spiritual values. Therefore, it is important to make adjustments to the national education system to balance technological advancements with the strengthening of character, social values, and the role of the family in the educational socialization process, so that education in Indonesia remains focused on forming individuals who are knowledgeable and have good character.